2006
DOI: 10.1183/09031936.06.00078405
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of the Smad signalling pathway: implications for COPD pathogenesis

Abstract: Pulmonary emphysema, as a feature of chronic obstructive pulmonary disease (COPD), is characterised by destruction of alveolar tissue. The present authors previously demonstrated reduced decorin expression in the peribronchial area of COPD patients, reflecting an altered extracellular matrix (ECM) modulation. Decorin transcription is regulated by the transforming growth factor (TGF)-b-Smad pathway, the key intracellular signal route for initiation of ECM component gene transcription. Whether this pathway is ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
56
2
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 27 publications
(42 reference statements)
4
56
2
1
Order By: Relevance
“…Loss of decorin in the lung may contribute to loosening of the collagen fibre network and higher levels of active transforming growth factor-b. As we have shown that decorin is consistently reduced in its presence and production in COPD [33,34,43], it will be of interest to evaluate whether a humoral autoimmune response may be involved. The next step is to also perform ELISPOT analysis on lung tissue to find out whether these anti-decorin IgG antibody-producing cells are also prominent in the lungs of COPD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of decorin in the lung may contribute to loosening of the collagen fibre network and higher levels of active transforming growth factor-b. As we have shown that decorin is consistently reduced in its presence and production in COPD [33,34,43], it will be of interest to evaluate whether a humoral autoimmune response may be involved. The next step is to also perform ELISPOT analysis on lung tissue to find out whether these anti-decorin IgG antibody-producing cells are also prominent in the lungs of COPD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Given the previous results of LEE et al [14], our own recent data regarding autoantibodies against elastin, collagen and decorin [21,32], and our previous findings regarding a decreased presence of decorin in COPD [33,34], we chose elastin, collagen and decorin as lung-specific antigens in this study.…”
mentioning
confidence: 99%
“…Decreased expression of TGF-b1, TbRI, and Smad3 has been reported in lung tissue specimens from patients with stage II COPD compared with normal control subjects (60). Moreover, cultured pulmonary fibroblasts from patients with emphysema show reduced response to TGF-b1 stimulation accompanied by increased levels of inhibitory Smad7 (Smad2/3 inhibitor) and reduced Smad3 activation, although TGF-b ligand production is increased (61).…”
Section: Abnormalities In Genes Involved In Tgf-b-smad Signaling Are mentioning
confidence: 99%
“…The main pathological change of emphysema is the destruction of extracellular matrix (ECM) components around the alveoli (Zandvoort et al 2006). It is associated with the imbalance of proteinase and antiproteinase activity which progressive proteolytic destruction without adequate repair.…”
mentioning
confidence: 99%
“…Tissue inhibitor of metalloproteinase (TIMP-1) is an important anti-protease of MMP-2 and MMP-9 in the lung. Another key modulating factor, transforming growth factor-β (TGF-β ), also affects the expression of ECM components (McGowan et al 1997;Morris et al 2003;Zandvoort et al 2006).…”
mentioning
confidence: 99%